Design and Implementation of a Production Forest Monitoring Information System in Central Sulawesi Province - Syahrullah, Syahrullah; Najar, Abdul Mahatir; Ngemba, Hajra Rasmita; Hendra, Syaiful (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Kesatuan Pengelola Hutan (KPH) Dolago Tanggunung, as one of the production forest managers in Central Sulawesi, faces serious challenges such as illegal logging, forest encroachment, and a high risk of forest fires. The complexity of managing production forests in this region is further hindered by manual data collection and reporting processes, which pose significant limitations. This study develops a Production Forest Management and Monitoring Information System aimed at improving efficiency in recording and monitoring production forests using the Agile-Scrum methodology, allowing for incremental development based on user needs. The system is designed as a web-based platform with key features including data collection for fire-prone areas, illegal logging incidents, and forest encroachment, as well as integration with spatial data visualization technology. Testing results indicate that the system enhances data recording efficiency, transparency in reporting, and accelerates response to on-site incidents. The implementation of this system is expected to support data-driven decision-making and strengthen sustainable forest management.